PANGGILAN KASIH KRISTUS DALAM KELUARGA KATOLIK DI PAROKI SANTO MICHAEL TOBADAK - Anryanto Ekstrella Limbongan; Carolus Patampang (LP2M STIKPAR Toraja, 2024)
Family is the first and foremost an opportunity, to proclaim the love and the light of gospel and the joy of Christ’s love in the family which is also the joy of the Church. Through his article, Pope Francis invites Christian Families to appreciate the gift of marriage and family, persevering in love that is strengthened by the values of generosity, commitment, loyalty and patience. Many of Christian Families still lack and do not understand the essence and the calling of marriage and have a family. Hence, this article aims to provide an understanding of the vocation and the meaning of marriage and family. This article composed using a qualitative research method phenomenological research design and employs data collection techniques such as documentation studies, observations, and interviews. This research reveals that the Catholic Families in center of Tobadak Paris still understand the meaning of family and marriage as a culture or responsibility that have to fulfill, in meaning that they work for their family, take their kids to school, and life together in a same house. Similarly, their understanding about life religiously is praying, have faith, and go to church at Sunday morning as a responsibility. Consequently, the calling of Christian family is very important to be understood and responded to in manner. As well as known the role of Catholic family to be involved in church and social life service.